Bending Opinion Essays on Persuasion in the Public Domain - Haaften, van, T.; Jansen, H.; Jong, de, J.; Koetsenruijter, W. (LUP Academic, 2011)
With communication playing an increasingly important role in contemporary society, rhetoric appears to have gained in influence and importance. The ancients knew all along: power belongs to those who know how to use their words. Nowadays, we know that rhetoric pervades all discourse. There is no communication without rhetoric. In a society with ever-increasing amounts of information, and with media whose significance cannot be overestimated, we need to know all the mechanisms playing a role in the gathering, making and reporting of information and opinions, and its processing by an audience. Rhetoric is, from both a practical and a theoretical perspective, essential to the conduct, analysis and evaluation of public debates. After all, the idea of democracy is closely intertwined with the ideal of transparent decision-making on the basis of open, informed discussions in the public domain, in political, organizational and journalistic discourse. Bending Opinion cites a host of relevant examples, from Barack Obama to Geert Wilders, as well as compelling case studies.